The diagnostic value of endobronchial ultrasound-guided transbronchial needle aspiration for bronchial anthracosis/anthracofibrosis with mediastinal enlarged lymph node - Xiao Li; Jinbing Pan; Ying Ren; Pei Wang; Guannan Sun (Frontiers in Medicine)
ObjectiveTo explore the value of endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) in patients of bronchial anthracosis (BAC)/bronchial anthracofibrosis (BAF) with enlarged mediastinal lymph nodes.MethodsA retrospective analysis was conducted on 5,589 bronchoscopies performed between January and December 2023. Among them, 62 patients were diagnosed with BAC, including 30 cases of BAF. Patients were categorized into BAF and non-BAF groups. Clinical data, laboratory findings, high-resolution computed tomography (HRCT) results, bronchoscopic features, and EBUS-TBNA outcomes were analyzed and compared between the two groups.ResultsThe overall incidence rates of BAC and BAF were 1.11 and 0.54%, respectively, with BAF accounting for 48.4% of all BAC cases. Compared to the non-BAF group, the BAF group exhibited higher frequencies of bronchial stenosis, mediastinal lymphadenopathy, and lymph node calcifications on HRCT. EBUS-TBNA cytology predominantly revealed lymphocytic infiltration and pigment-laden macrophages, with some findings of granulomatous inflammation and malignant cells. There was no significant difference in the overall diagnostic yield of EBUS-TBNA between the two groups.ConclusionEBUS-TBNA is a highly valuable diagnostic tool for differentiating BAC/BAF with mediastinal lymphadenopathy. It provides crucial pathological insights, especially in cases potentially involving malignancy or granulomatous disease.